Halal Culture in the Digital Sphere: A Semiotic Analysis of Culinary Reviews on Social Media - Narita Pratiwi; Eva Leiliyanti; Nurbaity; Nurul Adha Kurniati (Raja Zulkarnain Education Foundation, 2025)
PThis study investigates how halal values and images are represented on social media, particularly through culinary reviews on the TikTok platform. In the context of urban Muslim communities, the halal label serves not only as a marker of adherence to religious teachings but also as a representation of evolving culture and identity. Through a semiotic analysis of Ferdinand de Saussure, this study reveals how visual and narrative symbols are used by content creators to construct the meaning of halal in the digital space. The research findings indicate that halal imagery on TikTok does not always refer to official certification, but rather to social construction and perceptions of trust formed through digital narratives. This phenomenon reflects the commodification of halal, where religious values are reproduced as communication and marketing strategies within the context of digital capitalism.